Use of Fast Gamma Magnetic Stimulation Over the Left Prefrontal Dorsolateral Cortex for the Treatment of MCI and Mild Alzheimer's Disease: A Double-Blind, Randomized, Sham-Controlled, Pilot Study - Mimenza-Alvarado, Alberto José; Aguilar-Navarro, Sara Gloria; Martinez-Carrillo, Francisco M.; Ríos-Ponce, Alma E.; Villafuerte, Gabriel (Frontiers in Neurology, 2021)
Background: AD animal models have shown a reduced gamma power in several brain areas and induction of these oscillations by non-invasive methods has been shown to modify several pathogenic mechanisms of AD. In humans, the application of low intensity magnetic fields has shown to be able to produce neural entrainment at the magnetic pulse frequency, making it useful to induce gamma frequencies. Objective: To assess if the application of fast gamma magnetic stimulation over the left prefrontal dorsolateral cortex would be a safe and well tolerated intervention that could potentially improve cognitive scores in subjects with mild cognitive impairment and mild Alzheimer’s disease. Methods: In these randomized, double-blind, sham controlled study participants were assigned to either receive daily sessions two times a day of active or sham FGMS for 6 months. Afterwards, measurements of adverse effects, cognition, functionality, and depression were taken. Results: Thirty-four patients, seventeen in each group, were analyzed for the primary outcome. FGMS was adequately tolerated by most of the subjects. Only 4 patients from the active FGMS group (23.52%) and one patient from the sham FGMS group (5.88%) presented any kind of adverse effects, showing no significant difference between groups. Nevertheless, FGMS did not significantly change cognitive, functionality or depressive evaluations. Conclusion: FGMS over the left prefrontal dorsolateral cortex applied twice a day for 6 months resulted to be a viable intervention that can be applied safely directly from home without supervision of a healthcare provider. However, no statistically significant changes in cognitive, functionality or depression scores compared to sham stimulation were observed.